Un modello socioeconomico per la bioregione delle Alpi Apuane - Fabio Baroni (Scienze del Territorio, 2018)
In an area full of resources not fully enhanced, due to an economic model strongly dominated by marble quarrying (unsustainable both for its magnitude and modalities), it is possible to build an alternative if we focus on  local heritage. A new development model based on the systematisation, integration and enhancement of heritage resources is now pushed through by the sensibility, vision and initiative of local socioeconomic actors, steadfast in their sense of belonging to the Apuan territory, conscious of the unsustainability of the current economic model and capable of cooperating to make the best use of their territorial capital. The conception of an integrated sustainable development project for the Apuan bioregion is developed along strategic axes and multi-sector actions addressing the issue of local economy reconversion through an integrated perspective, taking also into consideration the necessity of reabsorbing the workforce currently employed in quarrying industry.